The deadly consequences of labor scarcity: Evidence from hospitals - Oliver Schlenker (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
This paper estimates the impact of nursing shortages in hospitals on healthcare provision and patient outcomes by exploiting a strong and stable appreciation of the Swiss franc in 2011. Due to collective bargaining hindering wage adjustments in the German healthcare sector, cross-border wage differentials increased and led to a significant outflow of German registered nurses to Switzerland, causing a 12.5% reduction in nurse staffing rates in German hospitals near the border. Using a matched difference-in-differences approach, I find that hospitals responded by decreasing care intensity, leading to a 12% decrease in surgeries. Although hospitals are increasingly performing triage, also patients with high medical needs - such as elderly and emergency cases - face a reduction in care and, consequently, a stark increase in mortality rates, resulting in a measurable decline in regional life expectancy.
urn:nbn:de:bsz:352-2-1ii51x0tstwlz2
Keywords: F22; I18; J22; J31; J61; I11; R23; 320; Labor scarcity; cross-border commuting; wage differentials; nurse shortages; healthcare provision; triage; patient outcomes